'You've come to children that are in care and given us the opportunity to get our voices heard': The journey of looked after children and researchers in developing a Patient and Public Involvement group. (21st May 2019) - Alderson, Hayley; Brown, Rebecca; Smart, Debbie; Lingam, Raghu; Dovey‐Pearce, Gail
Abstract: Background: Looked after children and care leavers (denoted as LAC) are often described as a 'hard to reach' group of young people, and their voices are rarely sought to inform academic research. Methods: This paper reports on experiences and reflections of a group of children and young people and academic researchers who developed a Patient and Public Involvement (PPI) group that was set up in the context of an ongoing health service intervention trial with LAC. Setting and participants: Eighteen qualitative semi‐structured interviews were conducted with seven LAC, the participation officer within a North East Children in Care Council and the four researchers involved in developing and facilitating the PPI group. PPI sessions (n = 9) each approximately 1 hour in length were conducted over an 18‐month period. Analysis: The qualitative interviews were transcribed verbatim. Thematic analysis was used to analyse the data, and direct quotes are used within the paper. Main outcomes: The LAC used the PPI group to produce a 5‐minute video to highlight why they think young people should be involved in research. Overall findings suggested that it was feasible to develop a research‐related PPI group with LAC. Findings from the research were used to co‐develop 'top tips' of working with vulnerable young people such as looked after children. Conclusion: This paper has shown that PPI with LAC can be done if a co‐production approach to research is taken. It also suggests that assumptions regarding the capabilities of young people as researchers need to be re‐evaluated.